2012
DOI: 10.1002/jbm.a.34532
|View full text |Cite
|
Sign up to set email alerts
|

pH‐responsive hydrogels with dispersed hydrophobic nanoparticles for the oral delivery of chemotherapeutics

Abstract: Amphiphilic polymer carriers were formed by polymerizing a hydrophilic, pH-responsive hydrogel composed of poly(methacrylic – grafted – ethylene glycol) (P(MAA-g-EG)) in the presence of hydrophobic PMMA nanoparticles. These polymer carriers were varied in PMMA nanoparticle content to elicit a variety of physiochemical properties which would preferentially load doxorubicin, a hydrophobic chemotherapeutic, and release doxorubicin locally in the colon for the treatment of colon cancers. Loading levels ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 57 publications
(123 reference statements)
0
55
0
Order By: Relevance
“…While hydrogels have been explored for delivering 51 payloads larger than 70 kDa, these studies have been limited to 52 non-pH responsive hydrogels in non-oral applications (Bertz et al,53 2013; Kidd et al, 2012;Kundu et al, 2012;Tokatlian et al, 2012). In 54 addition, most previously developed hydrogels are specific in the 55 size and type of drug they are able to efficiently load (Kamei et al,56 2009; Morishita et al, 2006Morishita et al, , 2002, requiring various modifications 57 for each different drug type (Hoare and Kohane, 2008;Liechty 58 et al, 2011;Schoener et al, 2013). 59 In this work, pH-responsive, lysine-based hydrogels were 60 synthesized from poly(L-lysine isophthalamide) (PLP) crosslinked 61 with L-lysine methyl ester (Fig.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…While hydrogels have been explored for delivering 51 payloads larger than 70 kDa, these studies have been limited to 52 non-pH responsive hydrogels in non-oral applications (Bertz et al,53 2013; Kidd et al, 2012;Kundu et al, 2012;Tokatlian et al, 2012). In 54 addition, most previously developed hydrogels are specific in the 55 size and type of drug they are able to efficiently load (Kamei et al,56 2009; Morishita et al, 2006Morishita et al, , 2002, requiring various modifications 57 for each different drug type (Hoare and Kohane, 2008;Liechty 58 et al, 2011;Schoener et al, 2013). 59 In this work, pH-responsive, lysine-based hydrogels were 60 synthesized from poly(L-lysine isophthalamide) (PLP) crosslinked 61 with L-lysine methyl ester (Fig.…”
mentioning
confidence: 97%
“…Thus, 39 hydrogels should be designed to retain and protect the drug in the 40 stomach, then release it in the small intestine. 41 The use of hydrogels in oral drug delivery has been investigated 42 for small molecules such as fluorescein (Schoener et al, 2011), 43 doxorubicin (Schoener et al, 2013), Rhodamine-B (Kim et al,44 2009), diltiazem hydrochloride (Frutos et al, 2010), and diclofenac 45 sodium (Yang et al, 2012), as well as proteins such as insulin 46 (5.8 kDa) (Wood et al, 2010), calcitonin (3.4 kDa) (Carr et al, 2010; (22 kDa) (Carr et al, 2010), interferon b (23 kDa) (Kamei et al,49 2009), and bovine serum albumin (69 kDa) (Kamei et al, 2009;Lin 50 et al, 2005). While hydrogels have been explored for delivering 51 payloads larger than 70 kDa, these studies have been limited to 52 non-pH responsive hydrogels in non-oral applications (Bertz et al,53 2013; Kidd et al, 2012;Kundu et al, 2012;Tokatlian et al, 2012).…”
mentioning
confidence: 99%
“…Rather, this new class of NP has the ability to respond to environmental, chemical, thermal or biological cues. 143,144 These "smart materials" release their therapeutic payload only upon being triggered by specific stimulus.…”
Section: Nanospheres and Nanocapsulesmentioning
confidence: 99%
“…The result showed that the carrier maintained cell viability, while MTX loaded on the nano-lipid inhibited the growth of both the cell lines. (ii) A novel pH-responsive hydrogel material was used as a carrier of anticancer drug [7]. This material can protect entrapped therapeutics in their collapsed state and permit diffusion of solvent and drug when in the swollen state.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, it is very important to find not only new chemotherapeutic drugs but also new strategies for administering them that could result more efficient and safer than conventional drugs and routes of administration. Today, controlled chemotherapeutic delivery systems, able to release the drug into the tumor during prolonged periods of time, are an option [6][7][8][9][10]. The literature reports the stabilization of anticancer drugs on several nanostructured materials: (i) For example, methotrexate (MTX) was stabilized on nanostructured lipid carriers for controlled delivery and cytotoxicity studies on human prostate cancer cells and ovarian human cancer cells [6].…”
Section: Introductionmentioning
confidence: 99%